INNOVATIVE TRANSFORMATIONS FOR SUSTAINABLE DEVELOPMENT IN NIGERIA’S MONETARY AND FISCAL POLICIES - Akamike, Joseph O.; Okonkwo, Osmond N. (African Journal of Social and Behavioural Sciences, 2024)
This paper examines the importance of sustainable economic development in Nigeria, focusing on key factors such as monetary and fiscal policies, infrastructure development, social welfare programs, and innovative transformations. It emphasizes the need for diversification, investment in human capital, infrastructure enhancement, and social inclusion for long-term prosperity. This paper also addresses challenges such as institutional capacity, regulatory environment, financial constraints, and socio-economic factors that hinder sustainable development efforts. This study being a review paper, aggregates findings of relevant empirical studies in monetary and fiscal policies in Nigeria to provide perspective to the current study’s objectives. It offers policy recommendations for advancing sustainable economic development, including diversification strategies, fiscal and monetary policy reforms, infrastructure investments, social welfare programs, public-private partnerships, human capital development, sustainable resource management, governance reforms, innovation promotion, and inclusive growth initiatives.